Hypofractionated radiotherapy with simultaneous tumor bed boost (Hi-RISE) in breast cancer patients receiving upfront breast-conserving surgery: study protocol for a phase III randomized controlled trial - Kairui Jin; Jurui Luo; Xiaoli Yu; Xiaomao Guo (Radiation Oncology, 2024)
Abstract Background The effectiveness and safety of moderately hypofractionated radiotherapy (HFRT) in patients undergoing breast-conserving surgery (BCS) has been demonstrated in several pivotal randomized trials. However, the feasibility of applying simultaneous integrated boost (SIB) to the tumor bed and regional node irradiation (RNI) using modern radiotherapy techniques with HFRT needs further evaluation. Methods This prospective, multi-center, randomized controlled, non-inferiority phase III trial aims to determine the non-inferiority of HFRT combined with SIB (HFRTsib) compared with conventional fractionated radiotherapy with sequential boost (CFRTseq) in terms of five-year locoregional control rate in breast cancer patients undergoing upfront BCS. A total of 2904 participants will be recruited and randomized in a 1:1 ratio into the HFRTsib and CFRTseq groups. All patients will receive whole breast irradiation, and those with positive axillary nodes will receive additional RNI, including internal mammary irradiation. The prescribed dose for the HFRTsib group will be 40 Gy in 15 fractions, combined with a SIB of 48 Gy in 15 fractions to the tumor bed. The CFRTseq group will receive 50 Gy in 25 fractions, with a sequential boost of 10 Gy in 5 fractions to the tumor bed. Discussion This trial intends to assess the effectiveness and safety of SIB combined with HFRT in early breast cancer patients following BCS. The primary endpoint is locoregional control, and the results of this trial are expected to offer crucial evidence for utilizing HFRT in breast cancer patients after BCS. Trial registration This trial was registered at ClincalTrials.gov (NCT04025164) on July 18, 2019.